Impact of Workplace Violence on Organizational Productivity in Nepalese Commercial Banks - Bhujel, Anjan; Pradhan, Sumit (Nepalese Journal of Management, 2024)
This study examines the impact of workplace violence on organizational productivity in Nepalese commercial banks. The dependent variable of the study is organizational productivity. Similarly, the selected independent variables are work-related harassment, customer frustration, long hours and over works, stress and high pressure, and employee conflicts. The primary source of data is used to assess the opinions of the respondents regarding work-related harassment, customer frustration, long hours and over works, stress and high pressure, employee conflicts, and organizational productivity. The study is based on primary data of 140 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of workplace violence on organizational productivity in Nepalese commercial banks. The study showed that work-related harassment has a negative impact on organizational productivity. It indicates that harassment in working environment leads to decrease in organizational productivity. Similarly, customer frustration has a negative impact on organizational productivity. It indicates that increase in frustration among the employees leads to decrease in organizational productivity. However, long hours and over works have a positive impact on organizational productivity. It indicates that long working hours and overwork leads to increase in organizational productivity. In addition, stress and high pressure has a negative impact on organizational productivity. It indicates that higher the stress and pressure, lower would be the organizational productivity. Further, employee conflicts has a negative impact on organizational productivity. It indicates that increase in employee conflict leads to decrease in the level of organizational productivity.